Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Depth and temperature associations of haddock Melanogrammus aeglefinus off southern Newfoundland - R. Rogers; S. Rowe; M. J. Morgan (Journal of Fish Biology, 2016)
Using data collected as part of offshore surveys conducted during 1972–2013, haddock Melanogrammus aeglefinus association patterns with depth and temperature in southern Newfoundland waters, the northern extremity of the species' range in the western Atlantic Ocean, were quantified. They were typically concentrated in the deep warm waters along the narrow shelf slope in North‐west Atlantic Fisheries Organization Divisions 3O and 3P with individuals moving seasonally into the shallow waters of the banks as they warmed. While M. aeglefinus were found over a range of depths and temperatures, they were primarily located at depths deeper and temperatures warmer than the median sampled. Analyses demonstrated that of the two hydrographic variables assessed, temperature was most influential in structuring distribution, with individuals appearing to change depth in order to maintain similar temperature throughout the year. Melanogrammus aeglefinus were found predominantly in temperatures of c. 4–8° C which often represented some of the warmest waters available. Differences in fish‐habitat association patterns in relation to sex or maturity status were not readily apparent from the analyses. Warming conditions off Newfoundland and Labrador in recent years might be predicted to improve local M. aeglefinus productivity.

Chemical Contaminants and their Effects in Fish and Wildlife from the Industrial Zone of Sumgayit, Republic of Azerbaijan - Carol D. Swartz; K.C. Donnelly; Arif Islamzadeh; Gilbert T. Rowe; William J. Rogers; Grigoriy M. Palatnikov; Arif A. Mekhtiev; Rafik Kasimov; Thomas J. McDonald; Jeffery K. Wickliffe; Bobby J. Presley; John W. Bickham (Ecotoxicology, 2003)

Acute and Genotoxic Effects of Baku Harbor Sediment on Russian Sturgeon, Acipenser guildensteidti - J. W. Bickham; G. T. Rowe; G. Palatnikov; A. Mekhtiev; M. Mekhtiev; R. Y. Kasimov; D. W. Hauschultz; J. K. Wickliffe; W. J. Rogers (Bulletin of Environmental Contamination and Toxicology, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Resistance exercise training and the orthostatic response - John P. McCarthy; Marcas M. Bamman; Janice M. Yelle; Adrian D. LeBlanc; Roger M. Rowe; Michael C. Greenisen; Stuart M. C. Lee; Elisabeth R. Spector; Suzanne M. Fortney (European Journal of Applied Physiology, 1997)